Amplop Terbang: Religio-Cultural Relations among the Pilangrejo Peoples - Alyyah, Arum Kholifatul (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2018)
This article aims to find out the religio-cultural relations in the amplop terbang activities on the Pilangrejo people. This study used a qualitative approach to the method of interviews conducted in the Pilangrejo Village community. The results show that: First, the amplop terbang that develop in the Pilangrejo community is a form of communication between human beings in the form of symbols using envelope media. Second, messages of religious teachings, ethical values, and prevailing norms are conveyed to citizens. Third, religious and cultural relations produce values of religiosity in people's daily lives. The most prominent value is the form of devotion to Allah Swt by loving each other. The peoples can build a life of mutual respect and side by side peacefully.